Impact assessment of plug-in electric vehicles on distribution networks (2011)
It is expected that electric vehicles market growth comes ahead due to ecological concern and energy efficiency maximization. As Plug-In Hybrid Electric Vehicles are by now the up to date development in the electric vehicles area and being aware of its plug to grid skills, it can be inferred that the new loads these represent could affect current electricity networks. This project presents an alternative method to determine this load based on a statistical approach using random variables but also assesses the impact of incorporating this new burden not only from a steady state perspective but also from a spectral viewpoint.